Studying the mechanism of sperm DNA damage caused by folate deficiency. Issue 3 (24th December 2021) - Wang, Wei; Peng, Meilin; Yuan, Hongfang; Liu, Chunyan; Zhang, Yuan; Fang, Yiwei; Su, Yufang; Zhang, Xinzong; Zhang, Huiping; Tang, Yunge; Zhao, Kai
Abstract: Sperm DNA injury is one of the common causes of male infertility. Folic acid deficiency would increase the methylation level of the important genes, including those involved in DNA double‐strand break (DSB) repair pathway. In the early stages, we analysed the correlation between seminal plasma folic acid concentration and semen parameters in 157 infertility patients and 91 sperm donor volunteers, and found that there was a significant negative correlation between seminal folic acid concentration and sperm DNA Fragmentation Index (DFI; r  = −0.495, p  < 0.01). Then through reduced representation bisulphite sequencing, global DNA methylation of sperm of patients in the low folic acid group and the high folic acid group was analysed, it was found that the methylation level in Rad54 promoter region increased in the folic acid deficiency group compared with the normal folic acid group. Meanwhile, the results of animal model and spermatocyte line (GC‐2) also found that folic acid deficiency can increase the methylation level in Rad54 promoter region, increased sperm DFI in mice, increased the expression of γ‐H2AX, that is, DNA injury marker protein, and increased sensitivity of GC‐2 to external damage and stimulation. The study indicates that the expression of Rad54 is downregulated by folic acid deficiency via DNA methylation. This may be one of the mechanisms of sperm DNA damage caused by folate deficiency.